Design and development of Android-Based Clinic Service Application: myclinic - Christanto, Henoch Juli; Sutresno, Stephen Aprius; Rudyanto, Robby Sentya; Prihanto, Pijar Karisma; Artpinkan, Tamaria H; Othernima, Desi C; Alvalent, Derrel (Institute of Computer Science (IOCS), 2024)
This research addresses the pressing need to enhance healthcare accessibility and efficiency, particularly in the context of increasing demands and challenges in the healthcare sector. The background problem lies in the limited accessibility and inefficiencies present in traditional healthcare systems, exacerbated by factors such as geographical constraints and resource limitations. To overcome these challenges, this study introduces MyClinic, an innovative application designed to streamline healthcare processes and improve access to clinic service. Utilizing structured methodologies including BPMN, ERD, Use Case Diagram, and Class Diagram, MyClinic is systematically developed to offer clear functionality. Through Black Box Testing, the application's functionality is rigorously validated, demonstrating compliance with specifications and ensuring user satisfaction. By addressing these issues, MyClinic aims to revolutionize healthcare delivery, offering a solution that is efficient, accessible, and user-friendly. This research highlights the critical role of technology in addressing healthcare challenges and underscores the potential of innovative solutions like MyClinic to transform healthcare delivery in the digital age